Clinicopathological Features and Prognostic Factors of Renal Cell Carcinoma in Young Patients Under 45 Years: A Single-Center Retrospective Study - Gao Y; Yan H; Zhang T; Lu G; Ma L (Cancer Management and Research)
Yu Gao,1,* Haisheng Yan,2,* Tao Zhang,2 Guanjun Lu,1 Lianghong Ma1,3 1Urology Department of General Hospital of Ningxia Medical University, Yinchuan, 750004, People’s Republic of China; 2The First Clinical Medical College, Ningxia Medical University, Yinchuan, 750004, People’s Republic of China; 3Key Laboratory of Fertility Preservation and Maintenance of Ministry of Education, School of Basic Medical Sciences, Ningxia Medical University, Yinchuan, 750004, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lianghong Ma, Email mmm1770@163.comObjective: To explore the clinicopathological characteristics, diagnostic approaches, and therapeutic strategies for renal cell carcinoma (RCC) in young patients under 45 years of age, aiming to provide insights for early detection and improved prognosis.Methods: We retrospectively analyzed the clinical data of 150 RCC patients aged 18 to 45 years treated at the General Hospital of Ningxia Medical University from 2011 to 2023. Clinicopathological features, surgical outcomes, and long-term follow-up data were evaluated.Results: The study included 82 males and 68 females, with a mean age of 38.89 ± 5.56 years. Clear cell RCC was the most common subtype (72.6%), followed by chromophobe RCC (12%) and papillary RCC (4%). Other rare subtypes included XP11.2 translocation/TFE3 gene fusion - associated RCC (2.7%) and collecting duct RCC (0.7%). In terms of clinical staging, 89% of patients were classified as T1 stage. Follow - up data, ranging from 12 to 153 months, showed that 11 patients died of the disease and 14 exhibited metastasis. Postoperative glomerular filtration rate (GFR) and serum creatinine (CREA)) levels were lower than preoperative levels, and patients who underwent radical nephrectomy (RN) had worse renal function than those who underwent partial nephrectomy (PN). The 3 - year and 5 - year survival rates for the asymptomatic group were 100% and 97%, respectively, while for the symptomatic group, they were 94% and 83%, respectively. Single - factor Cox regression analysis revealed that symptoms, hypertension, clinical stage, pathological grade, and pathological type were independent risk factors for overall survival in young renal cancer patients.Conclusion: Young RCC patients present with unique clinicopathological characteristics and prognostic factors. Although the overall prognosis is relatively favorable, rare subtypes such as XP11.2 translocation/TFE3 gene fusion - associated RCC and collecting duct RCC are associated with worse outcomes. Early detection through regular physical examinations and prompt treatment are crucial for improving outcomes. PN should be prioritized when feasible, and effective management of comorbidities like hypertension is essential.Keywords: young patients, renal cell carcinoma, clinical features, pathological features, prognosis